Antipsychotics for negative and positive symptoms of schizophrenia: dose-response meta-analysis of randomized controlled acute phase trials - Michel Sabe (Nature Portfolio, 2021)
Abstract Determining the optimal antipsychotic target dose in acute phase treatment is of high clinical relevance. The effect of antipsychotics on negative symptoms should be taken into account because patients will often continue on the treatment received in the acute phase. Therefore, we conducted a formal dose-response meta-analysis of negative symptoms and positive symptoms based on a systematic review of fixed-dose randomized controlled trials (RCTs) that examined the effectiveness of antipsychotics for the acute exacerbation of schizophrenia. Forty RCTs included a total of 15,689 patients. The 95% effective doses per day for the 13 antipsychotics included and 3 long acting were mostly different for negative and positive symptoms: amisulpride (481 mg, 690.6 mg); aripiprazole (11.9 mg, 11 mg); asenapine (7.61 mg, 5.66 mg); brexpiprazole (2.1 mg, 4 mg); cariprazine (4 mg, 6.51 mg); haloperidol (6.34 mg, 7.36 mg); lurasidone (58.2 mg, 86.3 mg); olanzapine (15.5 mg, 9.52 mg); olanzapine long-acting injection (15.7 mg, 13.5 mg); paliperidone (7.2 mg, 7 mg); paliperidone long-acting injection (7.5 mg, 5.9 mg); quetiapine instant-release (264.2 mg, 316.5 mg); quetiapine extended-release (774 mg, 707.2 mg); risperidone (7.5 mg, 7.7 mg); risperidone long-acting injection (5.13 mg, 6.7 mg); sertindole (13.5 mg, 16.3 mg); and ziprasidone (71.6 mg, 152.6 mg). The shape of the dose-response curves varied across different drugs with most drugs showing a plateau at higher doses. Most dose-response curves suggested that the near-maximum effective doses could be in the lower-to-medium range of the licensed dose. Additional RCTs are necessary to establish the optimal dose.